Improvement in hypertrophic cardiomyopathy after using a high-fat, high-protein and low-carbohydrate diet in a non-adherent child with glycogen storage disease type IIIa - ÖZTÜRK HİŞMİ, BURCU (My University, 2022)
Background: Glycogen storage diseases type IIIa and b (GSDIII) are rare inherited metabolic disorders that are caused by deficiencies of the glycogen debranching enzyme, resulting in the accumulation of abnormal glycogen (\"limit dextrin\") in the muscles. The cardiac storage of limit dextrin causes a form of cardiomyopathy similar to primary hypertrophic cardiomyopathy. Treatment with a high fat diet is controversial but we report a positive outcome in a child with cardiomyopathy. Case presentation: A 9-year-old boy with GSDIIIa developed left ventricular hypertrophy at 4.3 years of age. A high-fat (50%), high protein (20%), low-carbohydrates (30%) diet was introduced. After 18 months, echocar-diogram, biochemical and clinical parameters improved (Creatine Kinase (CK), 1628-)1125 U/L; left ventricular outflow tract (LVOT), 35-)20 mmHg; interventricular septum (IVS), 21-)10 mm). The diet was abandoned for 2 years resulting in reversal of symptoms, but recommencement showed improvement after 6 months. Conclusion: A high fat, high protein and low carbohydrate diet was successful in reversing cardiomyopathy. This form of treatment should be considered in children with GSD IIIa with cardiomyopathy.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Natural Sciences; GENETİK VE KALITIM; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); GENETICS & HEREDITY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Genetik (klinik); Moleküler Biyoloji; Genetik; Genetics (clinical); Molecular Biology; Genetics; Glycogen storage disease type III; Hypertrophic cardiomyopathy; Diet therapy; MANAGEMENT; DIAGNOSIS; LIVER